Beyond Extremism: Muslim-Christian Dialogue in a Post-9/11 Era - Reynolds, Thomas (Théologiques)

(untitled) (Faculté de théologie et de sciences des religions, Université de Montréal, 2011)
Seeking to move beyond language of “extremism”, this article discusses some of the promises and perils of Muslim-Christian dialogue in an era after September 11, 2001. The author advocates for the public face of religion in secular societies, assesses several recent developments in Muslim-Christian engagements, and proposes steps for opening up a more fruitful contemporary collaboration between Muslims and Christians. Written from a Christian perspective, the article concludes by arguing for “dialogical openness” as a hopeful path toward interfaith mutuality.